2013
DOI: 10.1038/cddis.2013.415
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide generates reactive oxygen species and autophagy in MDA-MB231 cells. A soluble parthenolide analogue inhibits tumour growth and metastasis in a xenograft model of breast cancer

Abstract: Triple-negative breast cancers (TNBCs) are clinically aggressive forms associated with a poor prognosis. We evaluated the cytotoxic effect exerted on triple-negative MDA-MB231 breast cancer cells both by parthenolide and its soluble analogue dimethylamino parthenolide (DMAPT) and explored the underlying molecular mechanism. The drugs induced a dose- and time-dependent decrement in cell viability, which was not prevented by the caspase inhibitor z-VAD-fmk. In particular in the first hours of treatment (1–3 h), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 56 publications
5
100
0
Order By: Relevance
“…In previous studies (13,15), we showed that parthenolide induces generation of ROS in MDA-MB-231 cells. The aim of the present study was to individuate the ROS produced under parthenolide treatment to specify the modalities of their production and the role exerted in the induction of cell death.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In previous studies (13,15), we showed that parthenolide induces generation of ROS in MDA-MB-231 cells. The aim of the present study was to individuate the ROS produced under parthenolide treatment to specify the modalities of their production and the role exerted in the induction of cell death.…”
Section: Discussionmentioning
confidence: 83%
“…•-production in MDA-MB-231 cells as well (13,15), which could be responsible for the toxic effects caused by the drug. These effects consist in the depletion of thiol groups and glutathione, NF-κB inhibition, c-Jun N-terminal kinase (JNK) activation, dissipation of mitochondrial membrane potential (∆ψm) and necrotic effects (12,13).…”
Section: The Oxygen Radicals Involved In the Toxicity Induced By Partmentioning
confidence: 99%
See 3 more Smart Citations